Rekonstruksi Tari Rejang Dewa pada Tradisi Megebeg-Gebegan dalam Rangka Penguatan Identitas Budaya Tradisional Bali di Desa Tukad Mungga, Buleleng - Ni Made Ruastiti; Gede Yoga Kharisma Pradana; Ni Kadek Suryani; Arya Pageh Wibawa (Jurnal Pengabdian Masyarakat Waradin, 2026)
The Rejang Dewa is one of Bali's traditional cultures that has long been preserved in the Megebeg-Gebegan tradition. However, it is nonexistent as part of the Megebeg-Gebegan. This community service activity aims to reconstruct the Rejang Dewa Dance and strengthen local cultural identity. Specifically, this activity aims to reveal the crisis facing the Rejang Dewa dance in Megebeg-Gebegan (1), reconstruct the Rejang Dewa dance in the Megebeg-Gegeban (2), and analyze the contribution of Rejang Dewa in the Megebeg-Gebegan tradition (3). Data analysis was conducted qualitatively based on the achievements of participatory observation, interviews, choreography training, and workshops. The results: 1) the loss of pride among the local community and the difficulty in finding Rejang Dewa dancers indicate a crisis; 2) the reconstruction of the Rejang Dewa dance was carried out through replication and integration of art and education in PKM activities based on local cultural studies; 3) the reconstruction of the Rejang Dewa has impacted on strengthening the aesthetic aspects and the function of religion and fostering a sense of pride in the culture of the Tukad Mungga Village community.